Penguatan Adat dan Revitalisasi Dakwah Penelitian di Muara Lingkat, Kerinci-Jambi - Mahli Zainuddin Tago (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2013)
This article is derived from a fieldwork carried out in Muara Lingkat, Kerinci- Jambi. The people of Kerinci are ethnically classified as Malay sub-ethnic. Like other Malay people in Sumatra, the people of Kerinci incorporate the religion of Islam or Islamic Shari’a into their customary norms (adat). Customary norms have for centuries played pivotal roles in governing the communities in Muara Lingkat. Yet, the role of customary norms gradually decline in line with the rise of formal institutions in modern society. By analyzing some cases discovered in the field, such as communal conflicts, disputes in the communities, tensions within family members, and the like, the author assumes that that the roles of customary norms become increasingly marginalized and consequently, the role of religion in resolving the problems of the communities decreases. In order to revitalize the roles of customary laws in resolving the problems that the communities in Muara Lingkat face, the author proposes some steps: exploring and reformulating the essence of local customary norms; strengthening local adat institutions; and providing assistance for the communities in establishing adat institutions. Keywords: Islamic dakwah, customary norms, social harmony, kerinci.